Molecular confirmation of Hymenolepis hibernia in field mice (Apodemus sylvaticus) from St Kilda has potential to resolve a host-parasite relationship. Issue 3 (December 2018) - Sargison, Neil; Herman, Jeremy; Pilkington, Jill; Buckland, Peter; Watt, Kathryn; Chambers, Alex; Chaudhry, Umer
Abstract: Insular wildlife populations provide opportunities to examine biological questions in systems that are relatively closed and potentially tractable, striking examples being the long-term studies of ecology and evolution in the red deer and feral sheep populations on the Hebridean islands of Rum and St Kilda. In the case of parasitology, Understanding of parasitic infections insular wildlife populations in conjunction with knowledge of their origins has the potential to add a fresh perspective to disease control in humans and domestic animals. In the case of parasitology, understanding infections of insular wildlife populations, in conjunction with knowledge of their origins, has the potential to add a fresh perspective to disease control in humans and domestic animals. With this in mind, gross and molecular examination for the presence of cyclophyllidean tapeworms was performed on the viscera and rectal contents of 17 preserved specimens of Apodemus sylvaticus field mice and on the naturally voided faeces of a further four mice on the remote archipelago of St Kilda. Molecular speciation of hexacanth embryos extracted from the faeces of two mice, using nucleotide sequence analysis of the ribosomal cytochrome c-oxidase subunit-1, confirmed infection with Hymenolepis hibernia . Phylogenetic analysis showed that these were genetically distinct from Hymenolepis diminuta, previously reported in the insular A. sylvaticus mice, and from other published H. hibernia haplotypes. There was insufficient hymenolepidid tapeworm phylogeographic variation to resolve the origins of the co-evolved St Kilda mice, primarily due to a lack of published H. hibernia Cox-1 sequence data across the parasite's geographical range. Nevertheless, the Maximum Likelihood haplotype tree shows the potential for molecular parasitology to resolve a host-parasite relationship once more data become available. Morphological diagnostic features of zoonotic H. hibernia eggs are also described. Graphical abstract: Image 1 Highlights: First identification of Hymenolepis hibernia in Apodemus sylvaticus hirtensis mice. Molecular speciation of hexocanth eggs. Morphological description of Hymenolepis hibernia eggs. Maximum likelihood hymenolepidid tapeworm haplotype tree. Consideration of parasite origins and those of co-evolved hosts.